Effects of added phosphorus and zinc on yield and its components of corn - Abbas, Abdalla E.; Hamad, Muawia E.; Babiker, Hashim M.; Nour, Abdellatif E. (Gezira Journal of Agricultural Science; Vol 5 No 2 (2007), 2007)
Experiments were conducted for two seasons (2000/01 and 2001/02) to study the effects of added phosphorus and zinc fertilizers on yield and its components of corn( Zea mays L.) grown on Remaitab soil series, (fine, smectitic, isohyperthermic, Typic Haplusterts) at the Gezira Research Station Farm, Wad Medani, Sudan. Phosphorus was banded in the soil as triple superphosphate at three rates (0, 43 and 86 kg P 2 O 5 ha -1 ). Zinc, as zinc sulphate, was also banded at three rates (0, 5 and 10 kg Zn ha -1 ). Nitrogen was broadcast as a basal dose in the form of urea at a recommended dose of 86 kg N ha -1 . Experiments were arranged in a split-plot design with four replicates. The results indicated that applica-tion of both nutrients significantly (P < 0.05) increased the number of cobs ha -1 , the number and weight of grains/cob, 100 grain weight and grain yield. However, doubling the rate of P to 86 kg P 2 O 5 ha -1 did not result in a significant difference over that of 43 kg P 2 O 5 ha -1 for most parameters studied.  Application of both P rates (43 and 86 kg P 2 O 5 ha -1 ) each in combination with Zn rates (5 and 10 kg Zn ha -1 ) increased weight of grains per cob, 100 grain weight and grain yield as compared to other treatments. For attaining maximum yield, application of 43 kg P 2 O 5 ha -1 + 10 kg Zn ha -1 banded in the soil at sowing is recommended, in addition to the recommended rate of nitrogen on the Remaitab soil series.